Boo! Baa, La La La! - Boynton, Sandra (New York : Little Simon, an imprint of Simon & Schuster Childrens Publishing Division, 2021)
BOO! BAA, LA LA LA! From the beloved and bestselling Sandra Boynton comes a terrific new Halloween board book. A long-lost cousin of her classic Moo, Baa, La La La!, this delightful little story begins: On Halloween, the cow says BOO. She likes that word. Its something new. The littlest book-lovers and their families will enjoy following the gentle cow as she ventures out into the moonlit night, trying to discover who it was that replied to her "BOO" with a "BAA." The surprise ending is certain to delight everyone-young or old, feathered or furry. Told and illustrated with Sandra Boyntons celebrated charm and pizzazz, Boo! Baa, La La La! is a wonderful, not-scary treat, with all the markings of a Halloween classic. BOO!
Keywords: Halloween -- Juvenile fiction; Animal sounds -- Juvenile fiction; Halloween -- Fiction; Animal sounds -- Fiction